PERBANDINGAN AKTIVITAS ANTIOKSIDAN PADA MINUMAN INFUSED WATER DARI JERUK NIPIS, JERUK LEMON DAN JERUK KALAMANSI DENGAN METODE DPPH - Herlina Herlina; Elly Mulyani; Tri Wulandari (Jurnal Insan Farmasi Indonesia, 2022)
Oranges contain compounds that are eficacious as antioxidants which are great for preventing and counteracting free radicals. The purpose of this research is to determine the value of antioxidant activity of infused water drinks of variety oranges (lemon, lime and calamansi oranges). This research was conducted by making an infused water drink by soaking oranges fruits in cooled water and left overnight in the refrigerator. The antioxidant activity was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The data obtained then calculated the value of antioxidant activity and calculated the IC50 value. The results showed that infused water drinks from lemon, lime and calamansi oranges had very strong antioxidant activity seen from the IC50 values which was less than 50 ppm, where calamansi with antioxidant activity value of 28,92 ppm, then followed by lemon with antioxidant activity value of 27.46 ppm and finally lime with antioxidant activity value of 24,39 ppm.